Antiplasmodial Activity Is an Ancient and Conserved Feature of Tick Defensins - Cabezas-Cruz, Alejandro; Tonk, Miray; Bouchut, Anne; Pierrot, Christine; Pierce, Raymond J.; Kotsyfakis, Michalis; Rahnamaeian, Mohammad; Vilcinskas, Andreas; Khalife, Jamal; Valdés, James J. (Frontiers in Microbiology, 2016)
Ancestral sequence reconstruction has been widely used to test evolution-based hypotheses. The genome of the European tick vector, Ixodes ricinus, encodes for defensin peptides with diverse antimicrobial activities against distantly related pathogens. These pathogens include fungi, Gram-negative and Gram-positive bacteria, i.e., a wide antimicrobial spectrum. Ticks do not transmit these pathogens, suggesting that these defensins may act against a wide range of microbes encountered by ticks during blood feeding or off-host periods. As demonstrated here, these I. ricinus defensins are also effective against the apicomplexan parasite Plasmodium falciparum. To study the general evolution of antimicrobial activity in tick defensins, the ancestral amino acid sequence of chelicerate defensins, which existed approximately 444 million years ago, was reconstructed using publicly available scorpion and tick defensin sequences (named Scorpions-Ticks Defensins Ancestor, STiDA). The activity of STiDA was tested against P. falciparum and the same Gram-negative and Gram-positive bacteria that were used for the I. ricinus defensins. While some extant tick defensins exhibit a wide antimicrobial spectrum, the ancestral defensin showed moderate activity against one of the tested microbes, P. falciparum. This study suggests that amino acid variability and defensin family expansion increased the antimicrobial spectrum of ancestral tick defensins.